PENERAPAN ACTIVITY BASED COSTING PADA INDUSTRI PERHOTELAN DI INDONESIA - Halleina Rejeki Putri Hartono; Trisna Ayu Oktavia; Sugiharto Sugiharto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This study aims to determine the application of ABC in the hospitality industry in Indonesia, the challenges of implementing ABC in the hospitality industry in Indonesia, and actions to overcome these challenges. The method used is qualitative research with literature study. The object used is an industrial hotel in Indonesia. The comprehensive implementation of ABC in Indonesia is still not comprehensive, it is only limited to the calculation of the imposition of production prices. The loading process includes activities, activity levels, and cost drivers which are the basis for loading. The challenges are system implementation, limited capabilities, the relationship between drivers and activities are difficult to identify. Another challenge is that the size of the organization becomes the standard of relevance in implementing ABC. Not all organizations can apply ABC. The nature of the costs in ABC turns into variable costs. This causes short-term decisions to be distorted. Actions that can be taken are to innovate and develop DCS comprehensively.